1986
DOI: 10.1073/pnas.83.5.1276
|View full text |Cite
|
Sign up to set email alerts
|

A mammalian high mobility group protein recognizes any stretch of six A.T base pairs in duplex DNA.

Abstract: ABSTRACTa-Protein is a high mobility group protein originally purified from African green monkey cells based on its affinity for the 172-base-pair repeat of monkey a-satellite DNA. We have used DNase I footprinting to identify 50 a-protein binding sites on simian virus 40 DNA and thereby to determine the DNA binding specificity of this mammalian nuclear protein. a-Protein binds with approximately equal affinity to any run of six or more APT base pairs in duplex DNA, to many, if not all, runs of five AkT base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
205
0
5

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(220 citation statements)
references
References 32 publications
10
205
0
5
Order By: Relevance
“…By measuring the efficiency of invertasome assembly, we also did not find that HU or HMG1 was altering the helical repeat of supercoiled DNA (Haykinson and Johnson 1993; data not shown). A significant preference of HMG1 or HMG2 activity on AT-rich regions was also not observed by either Hin-mediated inversion or ligation assays, in contrast to a report on chicken HMG2a (Brown and Anderson 1986) and another subgroup of HMG proteins, HMGI/Y, which bind preferentially to runs of five or more A or T nucleotides (Solomon et al 1986;Russnak et al 1988;Thanos and Maniatis 1992).…”
Section: Dna Bending Mediated By Hmg1 and Hmg2mentioning
confidence: 65%
See 1 more Smart Citation
“…By measuring the efficiency of invertasome assembly, we also did not find that HU or HMG1 was altering the helical repeat of supercoiled DNA (Haykinson and Johnson 1993; data not shown). A significant preference of HMG1 or HMG2 activity on AT-rich regions was also not observed by either Hin-mediated inversion or ligation assays, in contrast to a report on chicken HMG2a (Brown and Anderson 1986) and another subgroup of HMG proteins, HMGI/Y, which bind preferentially to runs of five or more A or T nucleotides (Solomon et al 1986;Russnak et al 1988;Thanos and Maniatis 1992).…”
Section: Dna Bending Mediated By Hmg1 and Hmg2mentioning
confidence: 65%
“…Because A-tracts are associated with intrinsically curved D N A (for review, see Travers and Klug 1990;Hagerman 1992), and some members of the HMG protein family--HMGI/Y and chicken H M G 2 a --are known to preferentially bind to AT-rich regions of DNA (Brown and Anderson 1986;Solomon et al 1986;Russnak et al 1988;Thanos and Maniatis 1992), we wanted to determine whether the A-tracts in our recombination substrates influence the function of HMG proteins in these assays. For this purpose we used a substrate whose intervening segment is 63% GC-rich and contains only two AA or TT dinucleotides (pMS551-97.1).…”
Section: Hmg Proteins In Hela Nuclear Extract Can Substitute For H U mentioning
confidence: 99%
“…In cells with defective mismatch repair, SSRs are prone to develop genetic instability, so called microsatellite instability, as a result of insufficient DNA mismatch repair of spontaneous mutations in repeat motifs due to strand mispairing during DNA replication. 28 SSRs like poly(T) repeats 29 and poly(TC) repeats 30 can function as binding sites for regulatory proteins in upstream activation sequences. In several studies, deletion of SSRs from upstream promoter regions has been shown to reduce or eliminate transcriptional activity, whereas expansion of SSRs led to an increase of transcriptional activity, possibly due to alterations of binding of regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that loss of E-cadherin, a molecule involved in maintaining tissue integrity, is associated with progression in prostate cancer (Umbas et al, 1992(Umbas et al, , 1994 al., 1988, 1989) and the closely related HMGI-C (Manfioletti et al, 1991). Members of the HMG-I(Y) family are distinguished from other groups of HMG proteins by their ability to specifically bind to the minor groove of A: T-rich DNA sequences (Elton et al, 1986;Solomon et al, 1986), presumably similar to antitumour and antiviral drugs (netropsin, distamicin) and the dye Hoechst 33258 (Disney et al, 1989;Wegner et al, 1990). …”
mentioning
confidence: 99%